Causal effects of non-alcoholic fatty liver disease on osteoporosis: a Mendelian randomization study - Zhou, Yue; Ni, Yunzhi; Wang, Zhihong; Prud’homme, Gerald J.; Wang, Qinghua (Frontiers in Endocrinology, 2023)
Background: Osteoporosis (OP) is a systemic skeletal disease characterized by compromised bone strength leading to an increased risk of fracture. There is an ongoing debate on whether nonalcoholic fatty liver disease (NAFLD) is an active contributor or an innocent bystander in the pathogenesis of OP. The aim of this study was to assess the causal association between NAFLD and OP. Methods: We performed two-sample Mendelian randomization (MR) analyses to investigate the casual association between genetically predicted NAFLD (i.e., imaging-based liver fat content [LFC], chronically elevated serum alanine aminotransferase [cALT] and biopsy-confirmed NAFLD)and risk of OP. The inverse variant weighted method was performed as main analysis to obtain the casual estimates. Results: Imaging-based LFC and biopsy-confirmed NAFLD demonstrated a suggestive causal association with OP (odds ratio [OR]: 1.003, 95% CI: 1.001-1.004, P < 0.001; OR: 1.001, 95% CI:1.000-1.002, P = 0.031). The association between cALT and OP showed a similar direction, but was not statistically significant (OR: 1.001, 95% CI: 1.000-1.002, P = 0.079). Repeated analyses after exclusion of genes associated with confounding factors showed consistent results. Sensitivity analysis indicated low heterogeneity, high reliability and low pleiotropy of the causal estimates. Conclusion: The two-sample MR analyses suggest a casual association between genetically predicted NAFLD and OP.